Systemic Changes in Adults With a Fontan Circulation: Insights From the Plasma Proteome - Benjamin Kelly; Maren Ravndal; Peter Bach; Niklas Telinius; Tue Bjerg Bennike; Vibeke E. Hjortdal (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Despite multiple surgeries and extensive follow‐up, individuals with a univentricular heart have significant residual morbidity and mortality throughout life. By applying a state‐of‐the‐art characterization of the plasma proteome, this study aimed at providing a comprehensive insight into the proteomic impact of living with a Fontan circulation. Methods and Results This study enrolled individuals with a Fontan circulation and compared them 2:1 with healthy controls. Relative quantification of the levels of 2943 plasma proteins was performed using Olink Explorer 3072 panels. The unprecedented number of plasma proteins constitutes the most detailed characterization of the Fontan proteome to date. A total of 87 individuals, 58 with a Fontan circulation age 26 (23–38) and 29 healthy controls age 24 years (20–27) were included. Following quality control 2605 proteins were quantifiable. Of these, 513 were changed in the group with Fontan (424 increased and 89 decreased) after covariate adjustment for age, sex, and body mass index. Looking at the related biological function(s), a pathway enrichment analysis found that proteins involved in angiogenesis, bone and calcium homeostasis, metabolism, and inflammation and fibrosis increased, whereas proteins involved in cholesterol synthesis and muscle structure and function were decreased. Conclusions This study represents a small step in understanding the pathophysiological consequences of the Fontan circulation. Based on biological pathways and proteins displaying changes, we speculate local hypoxia to be a potential driver for multiple of the reported changes. This study provides the foundation and direction for future studies wanting to examine changes in detail or explore possible therapeutic targets.